New class of crosslinker-free nanofiber biomaterials from hydra nematocyst proteins - Bentele, Theresa; Amadei, Federico; Kimmle, Esther; Veschgini, Mariam; Linke, Philipp; Sontag-González, Mariana; Tennigkeit, Jutta; Ho, Anthony Dick; Özbek, Suat; Tanaka, Motomu (Scientific reports, 2019)
Nematocysts, the stinging organelles of cnidarians, have remarkable mechanical properties. Hydra nematocyst capsules undergo volume changes of 50% during their explosive exocytosis and withstand osmotic pressures of beyond 100 bar. Recently, two novel protein components building up the nematocyst capsule wall in Hydra were identified. The cnidarian proline-rich protein 1 (CPP-1) characterized by a “rigid” polyproline motif and the elastic Cnidoin possessing a silk-like domain were shown to be part of the capsule structure via short cysteine-rich domains that spontaneously crosslink the proteins via disulfide bonds. In this study, recombinant Cnidoin and CPP-1 are expressed in E. coli and the elastic modulus of spontaneously crosslinked bulk proteins is compared with that of isolated nematocysts. For the fabrication of uniform protein nanofibers by electrospinning, the preparative conditions are systematically optimized. Both fibers remain stable even after rigorous washing and immersion into bulk water owing to the simultaneous crosslinking of cysteine-rich domains. This makes our nanofibers clearly different from other protein nanofibers that are not stable without chemical crosslinkers. Following the quantitative assessment of mechanical properties, the potential of Cnidoin and CPP-1 nanofibers is examined towards the maintenance of human mesenchymal stem cells.
Gesehen am 29.01.2020